2016
DOI: 10.1158/1055-9965.epi-16-0506
|View full text |Cite
|
Sign up to set email alerts
|

The Prostate, Lung, Colorectal and Ovarian Cancer (PLCO) Screening Trial Pathology Tissue Resource

Abstract: Background Pathology tissue specimens with associated epidemiological and clinical data are valuable for cancer research. The Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial undertook a large-scale effort to create a public resource of pathology tissues from PLCO participants who developed a cancer during the trial. Methods Formalin-Fixed Paraffin-Embedded (FFPE) tissue blocks were obtained from pathology laboratories on a loan basis for central processing of tissue microarrays, with add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A major strength of the current analysis was the ability to appraise the roles of over 1,300 proteins. A vital next step in assessing the role of the plasma proteome in EOC risk and validating our findings will involve directly measuring the 26 proteins shortlisted by our study in EOC case and control sample collections that have pre-diagnostic and longitudinal follow-up biospecimens available such as the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial [33]. The pleiotropic associations observed at the 9q34.2 locus where eight of the ten SNPs associated with plasma protein levels were also associated with other traits leaves open the possibility that some of these traits, rather than the protein levels, may underlie the association with EOC risk.…”
Section: Discussionmentioning
confidence: 99%
“…A major strength of the current analysis was the ability to appraise the roles of over 1,300 proteins. A vital next step in assessing the role of the plasma proteome in EOC risk and validating our findings will involve directly measuring the 26 proteins shortlisted by our study in EOC case and control sample collections that have pre-diagnostic and longitudinal follow-up biospecimens available such as the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial [33]. The pleiotropic associations observed at the 9q34.2 locus where eight of the ten SNPs associated with plasma protein levels were also associated with other traits leaves open the possibility that some of these traits, rather than the protein levels, may underlie the association with EOC risk.…”
Section: Discussionmentioning
confidence: 99%
“…Our overall tumor sample acquisition rate (87%) is higher than that reported by previous studies. For example, the Prostate, Lung, Colorectal and Ovarian Cancer (PLCO) Screening Trial only reported a sample retrieval success rate of 47% [ 7 ], with the Nurses’ Health Study reporting success rates of 70–80% [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various large-scale cohort studies from around the world have established tumor tissue repositories to support innovative research [ 6 , 7 , 8 , 9 ]. Currently, there are no cohort studies in Canada with similarly available resources.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular pathological epidemiology, which has recently received considerable attention, aims to elucidate specific relationships between putative etiologic factors and cellular molecular alterations. In particular, the molecularly defined subtypes of neoplastic diseases, including endometrial cancer, 3 colorectal cancer (CRC), 4,5 lung cancer, 6 and breast cancer, 7 are often associated with specific risk factors, emphasizing the importance of characterizing critical molecular alterations in tumor cells. In CRC, multiple biomarkers have been used to address the complexity of the disease and define tumor subtypes 8,9 .…”
Section: Introductionmentioning
confidence: 99%